SPF (SUN PROTECTION FACTOR) MEASUREMENT BASED ON SUNSCREEN IMAGE ANALYSIS - Inggarwati, Devi
Exposure to UV (Ultraviolet) rays from the sun has significant impacts on humans, including the risk of skin cancer, premature aging, and erythema. Therefore, photoprotection is essential to prevent skin damage from sun exposure. Sunscreen remains the primary recommended photoprotection product. The effectiveness of sunscreen in protecting the skin from sun exposure, particularly UVB, is expressed in terms of SPF (Sun Protection Factor). However, existing SPF measurement methods are complex, expensive, and time-consuming. Thus, there is potential for measuring SPF through image processing. Essentially, measurements using optical sensors like cameras observe and capture the interaction of light with the test material. The UV filters in sunscreen interact with light through reflection and absorption. If the characteristics of the captured image can represent these reflection and absorption processes, the effectiveness of the UV filters can be determined. SPF measurement of sunscreen involves several stages: sample preparation, image acquisition, image pre-processing, image processing, and correlation extraction. The sample preparation stage includes determining the sample and setting the application dose. After that, images of the sample are captured, and initial image processing is conducted to eliminate noise in the images. The characteristic evaluated during the image processing stage is the intensity, specifically the relative intensity of the light reflected by hybrid sunscreens and the light absorbed by organic sunscreens. The results of this measurement show that image intensity and SPF values have an exponential relationship. The determination coefficients obtained are strong, with R² = 0.9452 for organic sunscreen and R² = 0.9759 for hybrid sunscreen. The estimated SPF values also show minimal differences from the actual SPF values, with the largest difference being 5.8 and the smallest difference being 1.1. However, this measurement method is limited to sunscreens with the same ingredient composition.